Environmental Living and Parenting Style Affects Glue Inhaling Behavior among Elementary Students - Yusniar Yusniar; Lita Andayani; Taufik Ashar (Journal of Health Promotion and Behavior, 2018)
Background: One of the deviant behaviors that occur nowadays in children is the behavior of inhalation. Inhalant is an alternative drug substitute that is affordable for children and can cause addiction. Inhalants can have an impact on health, the social environment and culture. This study aimed to determine the effects of environmental living and parenting style on the glue inhaling behavior among elementary school students in Sibolga, North Sumatera.Subjects and Method: This was a case-control study conducted in Sibolga, North Sumatera, in May 2018. A sample of 60 elementary students was selected for this study by purposive sampling. The dependent variable was glue inhaling behavior. Independent variables were environmental living and parenting style. The data were obtained by a questionnaire and analyzed by a multiple logistic regression.Results: Permissive or authoritarian parenting style increased glue inhaling behavior and it was statistically significant (OR= 31.50; 95% CI= 5.99 to 165.47; p<0.001). Risky environmental living increased glue inhaling behavior but it was statistically non-significant (OR = 1.80; 95% CI <0.01 to 1.01; p = 0.999).Conclusions: Permissive or authoritarian parenting style and risky environmental living increase glue inhaling behavior in elementary students.Keywords: glue inhaling behavior, environmental living, parenting styleCorrespondence: